2012
DOI: 10.3382/ps.2011-02109
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune response to yeast-derived carbohydrates in broiler chickens fed organic diets and challenged with Clostridium perfringens

Abstract: Necrotic enteritis (NE) caused by Clostridium perfringens is a reemerging disease of economic importance in areas of the world where antibiotic growth promoters have been banned. The effect of mannan-oligosaccharide (MOS) supplementation in organic diets of broilers challenged with C. perfringens on performance, gut morphology, and innate immunity was investigated. Three hundred Ross-308 broilers were fed antibiotic-free certified organic starter and grower diets. On d 14, birds were orally challenged with 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 51 publications
5
52
1
Order By: Relevance
“…A possible reason for this may be due to the birds not being challenged with pathogenic microbes at this point. This trial supports the VH findings of White, et al (2002) in pigs and Yitbarek et al (2012) and Sohail et al (2012) in broilers when feeding MOS. However, Iji et al (2001) and Zhang et al (2005) found that birds fed yeast cell wall fractions had longer VH than control birds at 21 days.…”
Section: Journal Of Applied Animal Nutritionsupporting
confidence: 91%
See 2 more Smart Citations
“…A possible reason for this may be due to the birds not being challenged with pathogenic microbes at this point. This trial supports the VH findings of White, et al (2002) in pigs and Yitbarek et al (2012) and Sohail et al (2012) in broilers when feeding MOS. However, Iji et al (2001) and Zhang et al (2005) found that birds fed yeast cell wall fractions had longer VH than control birds at 21 days.…”
Section: Journal Of Applied Animal Nutritionsupporting
confidence: 91%
“…When looking at CD, Zhang et al (2005), Yitbarek et al (2012) and Sohail et al (2012) found feeding MOS had no effect on CD in birds, as seen in this study. Santin et al (2001) also saw no effect of MOS at 42 days, however decreased CD was observed at seven days of age in broilers fed MOS.…”
Section: Journal Of Applied Animal Nutritioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Park et al (2008) reported that intestinal IEL levels of IL-1β transcripts were decreased in chickens co-infected with E. maxima and C. perfringens compared with single infection by either pathogen alone, while IL-6 transcipt levels were not affected following infection with either or both microorganisms. Similarly, Yitbarek et al (2012) reported that IL-6 expression in the intestinal ileum or cecal tonsils was unaffected in C. perfringens-infected chickens compared with uninfected controls, leading these authors to theorize that IL-6 is not involved in Toll-like receptor regulation of C. perfringens-induced NE. Eimeria infection of chickens also induces iNOS expression both in vitro and in vivo (Dalloul et al, 2005;Lee et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the inclusion of yeast product in broiler diets can increase the number of health-promoting bacteria like lactobacillus spp. (Roto et al, 2015) and decrease the number of pathogenic microbiota such as Clostridium (Yitbarek et al, 2012) and E. coli (Huff et al, 2007). In addition, some researchers (Dibner, 2004;Kim et al, 2014) have suggested that acidifiers can decrease the intestinal pH and maintain acidic conditions in the gut environment.…”
Section: Discussionmentioning
confidence: 99%